Neuroregulatory and clinical efficacy of auricular vagus nerve stimulation in elderly patients with chronic insomnia comorbid with functional dyspepsia: protocol for a randomized controlled trial - Zhou, Hao; Tang, Xing; Wang, Dan; Huang, Zubo; Zeng, Yue; Liu, Shanshan; Wang, Chao (Frontiers in Medicine, 2025)
ObjectiveThis study innovatively employs transcutaneous auricular vagus nerve stimulation (taVNS), a non-invasive physical therapy, to intervene in elderly patients with chronic insomnia (CI) comorbid with functional dyspepsia (FD). Through systematic investigation of the molecular mechanisms underlying vagus nerve pathway regulation in ameliorating intestinal inflammatory microenvironment and modulating central neurotransmitter homeostasis, this research aims to provide a novel, neuromodulation-based precision therapeutic approach characterized by favorable safety and tolerability for integrated management of geriatric comorbidities.Methods/designThis double-blind randomized controlled trial will enroll 60 elderly patients (60–85 years) meeting ICSD-3 criteria for CI and Rome IV criteria for FD. Using block randomization with computer-generated sequences, eligible participants will be allocated 1:1 to either active taVNS group (n = 30) or sham control group (n = 30). The CFDA-certified transcutaneous vagus nerve stimulator (Model tVNS501, Reach Medical, China; Registration No. SuXieZhun20212090050) will be positioned at standardized anatomical sites: the concha cymba (the inferior margin of the intersection between the superior and inferior crura of the antihelix within the cymba conchae), electrical stimulation will deliver with fixed parameters (frequency: 80 Hz, pulse width: 100 μs, pulse 40–60s). The active group will receive validated taVNS parameters, while the sham group will undergo identical procedures without electrical output. Interventions will be administered 30 min per session, 5 sessions weekly for 3 consecutive weeks. Primary endpoints include changes in Pittsburgh Sleep Quality Index (PSQI) and Nepean Dyspepsia Symptom Index (NDSI) at week 3. Secondary outcomes encompass Insomnia Severity Index (ISI), 36-Item Short Form Survey (SF-36), and serum biomarkers (pro-inflammatory cytokines IL-1β, IL-4, IL-6, TNF-α, hs-CRP, TGF-β; neurotransmitters Dopamine (DA), serotonin (5-hydroxytryptamine, 5-HT), norepinephrine (NE), Glutamate (Glu), γ-aminobutyric acid (GABA)). Safety profiles will be systematically evaluated using CTCAE v5.0 criteria, with all adverse events documented throughout the study.DiscussionThis study mitigate the adverse effects associated with the significant side effects of oral medications in elderly patients with CI comorbid with FD. It seeks to scientifically validate the clinical efficacy of taVNS therapy, elucidate its underlying anti-inflammatory and neuromodulatory mechanisms, and establish a multimodal evidence chain integrating “efficacy-inflammation-neuromodulation.” By doing so, this research provides a novel, convenient, scientifically validated, effective, and safe non-pharmacological therapeutic approach for elderly patients with CI and FD, it offers innovative insights and methodologies for the development of pharmaceuticals, medical devices, and related products.